Combination of Fractional Radiofrequency and Thermo-Contraction Systems for Facial Skin Rejuvenation: A Clinical and Histological Study. (20th June 2018) - Samadi, Aniseh; Nasrollahi, Saman Ahmad; Janani, Leila; Moosavi, Zahra Beigom; Hesari, Kambiz Kamyab; Kalantari, Arash Rezaie; Firooz, Alireza
Abstract: Background: Radiofrequency energy systems are popular options in the treatment of skin laxity and wrinkles. Fractional radiofrequency devices (FRFs) have increased the efficacy and safety. The thermo-contraction (TC) system is also a novel technology that can promote a marked lifting effect. Objectives: This trial was done to assess the safety and efficacy of a combination treatment using the FRF system and TC for facial skin rejuvenation. Methods: Fifteen female volunteers (mean age, 47.07 ± 8.83 years) received 3 FRF and 6 TC bipolar treatments in 3 weeks. Assessment methods included wrinkle grading by independent investigator using Glogau wrinkle scoring, objective measurement of depth, area, and volume of right nasolabial fold (using the VisioFace CSI software), thickness and echo-density of the dermis (using high-frequency ultrasound), and measurement of the skin biophysical parameters before and 3 months after last treatment. Histological assessment was also performed on 5 volunteer participants. Results: The clinical evaluation showed a significant improvement in Glogau wrinkle scoring after 3 months ( P value, 0.041). The area and volume of nasolabial folds were also significantly reduced ( P values, 0.026 and 0.031, respectively). Skin ultrasound showed a significant increase in echo-density of the dermis, which was confirmed by histological findings of an increase in dermal collagen content. Adverse reactions were all transient and mild in severity, and subjects were "moderately satisfied" with the treatment (Likert scale, 3.6 out of 5). Conclusions: The results of this trial showed that a combination therapy by FRF and TC bipolar systems is efficient and safe for facial skin rejuvenation. Level of Evidence: 4: